The The Influence of Trust and Transaction Security on Interest in Using The QRIS Payment System: Study: QRIS Users in Bandung City - Nabila, Alya Putri; Raharso, Sri; Tiorida, Ermina (Universitas Airlangga, 2025)
This study aims to determine the effect of trust and transaction security on interest in using the QRIS payment system (study on QRIS users in Bandung City). The development of technology and payment systems today has encouraged innovations, including the use of QRIS as an increasingly popular digital payment method. In this case, understanding the interaction between trust, security, and interest in use is very important. This study uses quantitative methods with a population of QRIS users in Bandung City. The sample was taken by purposive sampling by distributing questionnaires to 200 respondents. Data collection was done through a questionnaire with a five-point Likert scale. Data analysis includes validity, reliability, descriptive statistics, classical assumptions, multiple linear regression, hypothesis testing, and coefficient of determination testing. The results showed that the research instruments were valid and reliable. There is a strong correlation between trust variables and security variables on interest in using, with a contribution of 41.8%. This observation shows that trust and security have a positive and significant influence on interest in using the QRIS payment system in Bandung City. The managerial implications of the results of this study suggest that digital payment service providers, such as banks and financial technology companies, should prioritize improving the security and systems that users trust. This can be done by increasing information transparency, educating about digital transaction security, and strengthening consumer data protection systems. These steps will increase user interest and loyalty to QRIS payment systems and encourage wider adoption of QRIS in society.